Effect of thermo-oxidative aging on properties of e- glass fiber-reinforced epoxy composites - Khajeh, Amin (2016)
The present study aims to investigate the effect of thermo-oxidative aging on the mechanical, chemical, physical properties of EHG250-68-37 E-glass fiberreinforced epoxy preimpregnated. To achieve the proposed research objectives, laminates of EHG-68-37 fiberglass/epoxy prepreg were exposed 800 h in isothermal condition and aircirculating oven at 82 °C. It is noteworthy that, before aging, specimens were dried to constant weight under vacuum at 70 °C in accordance with ASTM D 5229/D 5229M due to hydrophilic matrix. The variations of mechanical properties (the elastic moduli, tensile strength, strain break, and toughness) were quantified by conducting tensile tests on both aged and un-aged specimens based on ASTM D3039. Chemical changes in composites due to thermo-oxidative aging were analyzed by, Dynamic mechanical analysis (DMA), Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared spectroscopy (FTIR). Physical degradation mechanisms resulting from sub-Tg aging were monitored by weight loss measurements as a function of time and Scanning Electron Microscope (SEM) to investigate superficial resin, cross sectional, and the cryofractured surface morphology. The showed the toughness, tensile strength and modulus of the composites were increased after pronounced aging conditions, 3.7%, 48%, and 59%, respectively. Whereas a decrease (0.22%) was observed in the strain break. DMA results revealed that the glass transition temperature and rubbery state modulus were increased as a result of the matrix densification. FTIR spectroscopy demonstrated the formation of carbonyl compounds around IR band 1735 cm-1 due to oxidation of the chemical structure of the aromatic ethers. SEM observations indicated the existence of minor superficial cracking, growth in size and number of voids, and poor fiber-matrix adhesion after aging. In addition, a minor mass change was observed from mass loss monitoring methods. The overall findings suggest that post-curing and oxidation enhanced the brittleness of the resin, leading to a significant decline in the useful structural life of the thin-skinned composite